Deprivations rarely come alone. Multidimensional poverty dynamics in Europe - Suppa, N (Oxford Poverty and Human Development Initiative (OPHI), 2023)
Despite multidimensional poverty measures becoming more popular, little is known about related dynamics at the micro-level. In this paper I propose a framework for the analysis of micro-level dynamics which are inherent to measures of multidimensional poverty. Specifically, in order to explore whether deprivations couple over time, I analyse differences in deprivation transition probabilities between multidimensionally poor and non-poor people. I argue that analysing entries and exits separately is important and that both analyses may be obtained from a single linear model per deprivation indicator. Advantages of the developed approach include that it (i) reflects and summarises relevant mechanisms, (ii) requires only short-run panel data and (iii) is suitable for monitoring purposes. Moreover, the approach may also be applied beyond multidimensional poverty analysis. I illustrate the approach using panel data of the European Union Statistics on Income and Living Conditions (EU-SILC) for more than 20 countries over 2016–2020. The presented evidence suggests that deprivations tend to couple over time. Empirical patterns are broadly time-stable, but vary across countries in magnitude. Implications include that coordinated policy programmes seem critical to overcome entrenched and prevent future deprivations.